Microscopic heterogeneity of plastic strain and lattice rotation in partially recrystallized copper polycrystals. (February 2020) - Lin, Fengxiang; Shi, Qiwei; Delannay, Laurent
Abstract: Partial recrystallization of highly deformed polycrystalline aggregates creates a bimodal grain size distribution, which improves ductility while maintaining relatively high strength. In this work, the microstructure evolution during isothermal annealing of cold rolled copper samples was investigated using electron backscattered diffraction (EBSD) and the macroscopic mechanical strength of partially recrystallized samples was measured under uniaxial tension. Different models were tested in order to reproduce both the macroscopic mechanical response and the microscopic strain field inside a sample with 41% recrystallized grains loaded inside a scanning electron microscope to allow in-situ EBSD mapping. Crystal plasticity based finite element modeling (CPFEM) performed on a 2D mesh conforming to the experimental microstructure was compared to 3D predictions on an idealized model microstructure.